Efficacy of Prophylactic Intra‐Aortic Balloon Pump Therapy in Chronic Heart Failure Patients Undergoing Cardiac Surgery. Issue 11 (21st February 2014) - Yildirim, Yalin; Pecha, Simon; Kubik, Mathias; Alassar, Yousuf; Deuse, Tobias; Hakmi, Samer; Reichenspurner, Hermann
Abstract This study investigated the efficacy of prophylactic intraoperative intra‐aortic balloon pump (IABP) usage in chronic heart failure patients with severely reduced left ventricular function undergoing elective cardiac surgery. Between January 2008 and December 2012, 107 patients with severely reduced left ventricular ejection fraction (LVEF <35%) received prophylactic intraoperative IABP implantation during open‐heart surgery. Surgical procedures performed were isolated coronary artery bypass grafting (CABG) in 35 patients (32.7%), aortic valve replacement in 12 (11.2%), mitral valve repair or replacement in 15 (14.0%), combined valve and CABG procedures in 27 (25.2%), and other surgical procedures in 18 (16.8%). Results and outcomes were compared with those in a propensity score‐matched cohort of 107 patients who underwent cardiac surgery without intraoperative IABP implantation. Matching criteria were age, gender, LVEF, and surgical procedure. Duration of intensive care unit (ICU) stay, duration of hospital stay, and 30‐day mortality were markers of outcome. In the IABP group, mean patient age was 69.1 ± 13.7 years; 66.4% (70) were male. All IABPs were placed intraoperatively. Mean duration of IABP application time was 42.4 ± 8.7 h. IABP‐related complications occurred in five patients (4.7%), including one case of inguinal bleeding, one case of mesenteric ischemia, and ischemia of the lower limb in three patients. No stroke or major bleeding occurred during IABP support. Mean durations of ICU and hospital stay were 3.38 ± 2.15 days and 7.69 ± 2.02 days, respectively, in the IABP group, and 4.20 ± 3.14 days and 8.57 ± 3.26 days in the control group, showing statistically significant reductions in duration of ICU and hospital stay in the IABP group (ICU stay, P = 0.036; hospital stay, P = 0.015). Thirty‐day survival rates were 92.5 and 94.4% in the IABP and control group, respectively, showing no statistically significant difference (P = 0.75). IABP usage in chronic heart failure patients with severely reduced LVEF undergoing cardiac surgery was safe and resulted in shorter ICU and hospital stay but did not influence 7‐ and 30‐day survival rates.